Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I've got the next question, we have the canonical standard symplectic form, $\omega_{std}$, given in coordinate form $\omega_{std}=\sum_{i=1}^{n} dq_i \wedge dp_i$, and I want to show that it's non-degenrate.

I.e, for $x=(x_1,...,x_n) \ \forall y=(y_1,...,y_n)$ if $\omega_{std}(x,y)=0$ then $x=0$.

So if I understnad correctly I get:

$$0=\omega_{std}(x,y)= \sum dx_i \wedge dy_i$$

Somehow I want to pick such that it will imply that every $x_i$ is zero, any hints what will make it? It's easy right? :-(


share|cite|improve this question
Your question is notationally confused. $\omega$ takes as inputs pairs of vectors of the form $v=(v_1,v_2,\ldots,v_{2n})$ where we can choose the basis so that $dx_i(v)=v_i$ and $dy_i(v)=v_{i+n}$. i.e. it is in $\Omega^2(\mathbb{R}^{2n})$ not $\Omega^2(\mathbb{R}^n)$. – Adam Apr 3 '12 at 18:04
I still don't see how to choose the $v'$ vector s.t $\omega(v,v')=0 \Rightarrow v=0$. – MathematicalPhysicist Apr 3 '12 at 18:29
up vote 1 down vote accepted

To do it by bare hands, I'd argue as follows. Given $x$ with the property that $\omega_{std}(x,y) = 0$ for all $y$, express $x$ in the basis $\partial q_i, \partial p_j$. So $x = a^i \partial q_i + b^j \partial p_j$ (with the Einstein summation convention) for some choices of $a^i$ and $b^j$. Our goal is to show that each $a^i = b^j = 0$.

Well, set $y = \partial p_k$. Then we get \begin{align*} 0 &= \omega_{std}(x,\partial p_k)\\ &= \sum (dq^i \wedge dp^i)(x,\partial p_k)\\ &= \sum dq^i(x)dp^i(\partial p_k) - dq^i(\partial p_k) dp^i(x) \end{align*}

Now, the basis $\{dq^i, dp^j\}$ is dual to $\{\partial q_i, \partial p_j\}$, so this sum isn't too hard to evaluate. The second term of the sum is identically $0$ since $dq^i(\partial p_k) = 0$. The first is $0$ unless $i = k$ since $dp^i(\partial p_k) = 0$ for $i\neq k$ and equals $1$ when $i = k$.

So, the sum reduced to a single term: $$0 = dq^k(x)dp^k(\partial p_k) = dq^k(x)$$

Finally, to evaluate $dq^k(x)$, recall $x = a^i \partial q_i + b^j \partial p_j$. So \begin{align*} dq^k(x) &= dq^k(a^i \partial q_i + b^j \partial p_j)\\ &= a^i dq^k(\partial q_i) + b^j dq^k(\partial p_j)\\ &=a^k\end{align*}

where the last step uses the fact that you're working in a dual basis. Putting this altogether, we just showed $0 = a^k$. Doing this for all $k$, and then using $y = \partial q_k$ to deal with the $b^j$ shows $x = 0$.

share|cite|improve this answer

The matrix of the quadratic form is in block form $\begin{pmatrix} 0 & I \\ -I & 0 \end{pmatrix}$ (where $I$ is the $n \times n$ identity matrix), which is nonsingular.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.